Ganodiesel: a new biodiesel feedstock from biomass of the mushroom Ganoderma lucidum - Mohamad Jahis, Besek Mariam; Zul Ilham; Supramani, Sugenendran; Sohedein, Mohamad Nor Azzimi; Ibrahim, Mohamad Faizal; Abd-Aziz, Suraini; Rowan, Neil; Wan Mohtar, Wan Abd Al Qadr Imad (Multidisciplinary Digital Publishing Institute, 2022)
There is a pressing demand for new sustainable eco-friendly approaches to producing green energy worldwide. This study represents the novel production of biodiesel feedstock from the medicinal mushroom Ganoderma lucidum QRS 5120 using state-of-the-art biotechnology tools. Response surface methodology (RSM) was used to enhance G. lucidum production in a repeated-batch fermentation strategy. By referring to the broth replacement ratio (BRR) and broth replacement time point (BRTP), RSM that was formulated using a central composite design (CCD) resulted in a significant model for all tested variables, which are exopolysaccharide (EPS), endopolysaccharide (ENS) and biomass, with BRR (%) of 60, 75 and 90, and BRTP (days) of 11, 13 and 15. The model was validated using the optimised conditions, and the results showed 4.21 g/L of EPS (BRR 77.46% and BRTP 12 days), 2.44 g/L of ENS (BRR 60% and BRTP 12.85 days), and 34.32 g/L of biomass (BRR 89.52% and BRTP 10.96 days) were produced. Biomass produced from the G. lucidum was subsequently used as feedstock for biodiesel production. Approximately 20.36% of lipid was successfully extracted from the dried G. lucidum biomass via a solvent extraction and subsequently converted to Ganodiesel through a transesterification process. The Ganodiesel produced fulfilled most of the international standards, i.e., US (ASTM D6751-08) and EU (EN 14214). Overall, this study demonstrates the optimised G. lucidum production and its lipid production as a new biodiesel feedstock.